Intra‐ocular diathermy forceps. Issue 4 (2nd December 2017) - van Overdam, Koen A.; Kilic, Emine; Verdijk, Robert M.; Manning, Sonia
Abstract: Purpose: The purpose of this study was to develop intra‐ocular diathermy forceps and test them on perfused porcine cadaver eyes. Methods: We designed two types of 23‐gauge intra‐ocular bipolar diathermy forceps by modifying commercially available membrane peeling forceps. In the first type, the emitting electrode is connected to one‐half of the core and the return electrode to the other half, with one jaw of the forceps attached to each half. In the second type, the emitting electrode is attached to the core and both jaws of the forceps, and the return electrode to the surrounding tube. We compared the new diathermy forceps to conventional intra‐ocular diathermy, on perfused porcine cadaver eyes. First‐order retinal artery and vein closure was confirmed both by a perfusion study and by histology of the treated vessels. Results: Type 1 diathermy forceps closed retinal arteries and veins more successfully (five of five and five of five successful treatments, respectively) than Type 2 diathermy forceps (five of five and four of five, respectively) and conventional diathermy (three of five and four of five, respectively). Less energy was used with Type 1 compared to Type 2 and conventional for artery closure (1.5 ± 0.0 versus 4.6 ± 3.3 versus 2.1 ± 0.8 joules, respectively) and vein closure (1.5 ± 0.0 versus 5.4 ± 4.6 versus 2.4 ± 0.8 joules, respectively). Histology of the treated vessels confirmed the perfusion study results. Conclusion: We designed two types of a new multifunctional intra‐ocular instrument with the ability to peel membranes and to grasp, compress and coagulate retinal blood vessels. Both types pose operational advantages compared to current conventional intra‐ocular diathermy.